Exploring Speech Acts on Get to Know by English Academy Videos of Ruangguru YouTube Channel - Arina Vionarsih; Otong Setiawan Djuharie (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
The rapid development of information technology in Indonesia has fostered the growing use of digital platforms in language learning, particularly YouTube as a contextual and easily accessible audiovisual medium. This study aims to identify and analyze the types of speech acts, based on Searle's classification, in the "Get to Know" video series from the English Academy on the Ruangguru YouTube channel, and to examine their functions in supporting the effectiveness of digital learning. Employing a descriptive qualitative approach, the study analyzed two purposively selected videos by transcribing instructors' utterances in full and systematically classifying them into representatives, directives, expressives, commissives, and declaratives. The findings reveal that representative speech acts dominate the videos (55 occurrences), functioning primarily to convey factual information and conceptual explanations. Directive speech acts (17 occurrences) provide instruction and motivation, whereas expressive speech acts (13 occurrences) build emotional rapport with the audience. Commissive and declarative speech acts were not identified. These findings indicate that the strategic use of speech acts enhances instructional communication, learner engagement, and motivation in video-based language learning. This study contributes to digital pragmatics by demonstrating how informative, persuasive, and expressive speech acts can be optimized in YouTube-based English language learning in Indonesia, and it offers practical implications for the design of digital educational content.